The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/trf.17249
|View full text |Cite
|
Sign up to set email alerts
|

A single‐center, retrospective analysis of 17 cases of hemolytic disease of the fetus and newborn caused by anti‐M antibodies

Abstract: Objective We aimed to summarize the laboratory findings and clinical features of hemolytic disease of the fetus and newborn (HDFN). Methods We retrospectively analyzed the data for 17 infants with anti‐M‐induced HDFN (anti‐M‐HDFN) diagnosed between June 2013 and May 2019. Their maternal history, neonatal diagnosis on admission, and laboratory test results were compared with those of 15 infants with HDFN involving the ABO blood group system, 15 infants with HDFN involving the Rh system, and 15 premature infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…6,7 Indeed, in individuals with D -/phenotype, RHCE proteins are not expressed on the RBC membrane, causing the production of allo-antibodies against CcEe antigens upon immune stimulus, which could lead to the development of HTR or HDN. [8][9][10] A rare number of individuals have been identified with a negative profile for RhCE antigens, hence the frequency of D -/is very low.…”
Section: Neonatal Hemolytic Anemia Due To the Mother's Rare Rhd -/Phe...mentioning
confidence: 99%
“…6,7 Indeed, in individuals with D -/phenotype, RHCE proteins are not expressed on the RBC membrane, causing the production of allo-antibodies against CcEe antigens upon immune stimulus, which could lead to the development of HTR or HDN. [8][9][10] A rare number of individuals have been identified with a negative profile for RhCE antigens, hence the frequency of D -/is very low.…”
Section: Neonatal Hemolytic Anemia Due To the Mother's Rare Rhd -/Phe...mentioning
confidence: 99%
“…They felt the need for information regarding plasma studies in the newborn, elution studies, and low-incidence antibody testing, and stated that a positive newborn DAT is nondiagnostic and requires further evaluation, as even a negative maternal IAT does not preclude the possibility of HDFN to a lowincidence maternal alloantibody They went on to state that contemporary and historical literature of larger case series found that in HDFN caused by anti-M the neonatal DAT is more frequently negative than positive. [2][3][4] Therefore, the positive DAT cited by Beck et al could theoretically lower one's suspicion for the cause of HDFN being solely due to anti-M. Additionally, when discussing any case of HDFN, but especially with anti-M where the antibody's isotype and reacting temperature are questionable, the testing methods including platform technology, temperature, and enhancement media are vital to the discussion. They went on to state that although this case could be an important addition to the growing body of evidence supporting anti-M as a cause of HDFN, further investigation and reporting are required to definitively establish this conclusion.…”
mentioning
confidence: 99%
“…2 Further, contemporary and historical literature of larger case series found that in HDFN caused by anti-M the neonatal DAT is more frequently negative than positive. [2][3][4] Therefore, the positive DAT cited by Beck et al could theoretically lower one's suspicion for the cause of HDFN being solely due to anti-M. In addition, when discussing any case of HDFN, but especially with anti-M where the antibody's isotype and reacting temperature can be in question, the testing methods including platform technology, temperature, and enhancement media are vital to the discussion.…”
mentioning
confidence: 99%